Popular School of Arts (Revista Apotheke, 2022)
This article discusses a teaching experience carried out during the course Internship in Visual Arts IV by the academic of the Degree in Visual Arts at the University of Caxias do Sul (UCS), Darlan Gebing Scheid, in the second half of 2021. The work was developed in a social project called Escola Popular de Artes carried out by Escola Tem Gente Teatrando, in Caxias do Sul – RS. During the semester, the group of students participating in the project was proposed to carry out a Cartography of the Self, proposing that the adolescents look at themselves, at the collective and at the place where they live so that they could create from these elements.
Keywords: Art; Education; Collage; Dadaism; Cartography